MENINGKATKAN PEMAHAMAN KONSEP ARAH MELALUI KEGIATAN PEMBELAJARAN EKSPLORASI, ELABORASI DAN KONFIRMASI TERHADAP ANAK TUNAGRAHITA RINGAN - OKTA FIRMANTO (Universitas Negeri Padang, 2015)
ABSTRACTThis research was initiated by the problem found in class IV indicating that student got difficulties in understanding the concept of direction. Instructed to do something related to right, left, in front of and behind direction, he was unable to follow the instruction given. This research was aimed at examining whether the activities of exploration, elaboration, and confirmation could increase the student's understanding on the concept of direction.This was an experimental research which applied Single Subject Research (SSR) method and A-B-A design. The data gathered were analyzed by using visual analysis of graphic. The number of instructions responded correctly was tallied. The variable was measured by using frequency technique.The percentage of the data overlapped in the activities of exploration, elaboration and confirmation was small. The smaller the number of the data overlapped the better the intervention affected the target behavior. Based on these results, it was concluded that the activities of exploration, elaboration, and confirmation could increase the student's understanding on the concept of direction. Therefore, it was recommended to the teachers to do the activities exploration, elaboration, and confirmation to introduce the concept of direction to the students with light metal retardation. Keyword: Anak tunagrahita ;konsep arah; kegiatan pembelajaran